Engineering the middle classes: State institutions and the aspirations of citizenship. (December 2022) - Bolt, Maxim; Schubert, Jon
The 'middle class' has become the subject of euphoric narratives of growth and improving standards of living around the globe, and the object of government interventions and social engineering. Government interventions may be ineffective, have unintended outcomes, or be left barely articulated. Yet the place of the middle classes as embodying national success, stability and modernity has taken on the power of common sense. Modern states have long made middle classes, and in turn been legitimated by them. Indeed, 'state' and 'middle class' are sharply normative concepts – bound up with ideals as much as ideas. They represent interrelated, morally loaded projects of demarcation, distinction and recognition. This special issue examines how state institutions make middle classes through such normative commitments, and how they are made by them in turn.